Correlation Level of Energy Consumption Level of Protein and Body Image Prevalency CED in Shafta High School Surabaya - Asti Pramesta Swari; Nur Hatijah; Nuning Marina Pengge; Annas Buanasita (Politeknik Kesehatan Kemenkes Surabaya, 2023)
One of the nutritional problems in adolescents is Undernutrition, which can be caused by inadequate energy and protein intake. A contributing factor to the lack of intake is body image. Undernutrition can lead to decreased learning concentration and have implications for future pregnancy. To determine the relationship between energy and protein consumption levels and body image with the prevalence of Undernutrition in Shafta Surabaya High School. This study is an analytical observational research using the SQ-FFQ 2-week form to determine energy and protein consumption levels and the BSQ form to assess body image. The percentage of female students with severe energy deficit consumption (52.9%), severe protein deficit consumption (41.2%), and positive body image (84.3%) is high. The prevalence of Undernutrition is 47.1%. The Spearman correlation test results show a significant relationship between energy and protein consumption levels and body image with Undernutrition prevalence. Most respondents have severe energy and protein deficit, positive body image, and a high prevalence of Undernutrition. There is a significant relationship between energy and protein consumption levels and body image among female adolescents Further research is needed to explore adolescents' knowledge regarding the ideal body shape.